Barriers and facilitators of behavior change for the sustainable harvesting of Sphagnum magellanicum moss in southern Chile - Leiva-Pinto, Eduardo; Alarcón, Cecilia; Tartakowsky, Viviana; Zúñiga, Manuela; Benítez-Mora, Alfonso; Herrera, Jaime; León, Carolina A. (Frontiers in Conservation Science, 2026)
This article addresses the critical global challenge of promoting sustainable practices for the use of renewable natural resources. In this research this is studied by analyzing the barriers and facilitators of behavior change in the sustainable harvesting of Sphagnum magellanicum moss in the Los Lagos Region of Chile. This study fills a significant knowledge gap by exploring how to design and implement interventions that enhance individual and collective capability to manage resources. Employing a qualitative methodology, the research draws on two complementary theoretical frameworks: Bronfenbrenner’s Ecological Model and Michie’s Behavior Change Wheel (COM-B system). The findings reveal emergent categories within the COM-B framework, highlighting specific barriers and facilitators to the adoption of pro-environmental behaviors. Furthermore, the study demonstrates the intricate interplay between these factors and the hierarchical systems of Bronfenbrenner’s Ecological Model. This research provides practical information for policy makers and practitioners seeking to foster sustainable behaviors, contributing to global efforts in environmental conservation, and sustainable resource management.